High second-order nonlinear response of platinum nanoflowers: the role of surface corrugation. Issue 6 (22nd January 2016) - Ngo, Hoang Minh; Lai, Ngoc Diep; Ledoux-Rak, Isabelle
Abstract : We report the Harmonic Light scattering properties of PtNFs for six different diameters (∼7.0; 8.0; 10.0; 14.0; 20.0 and 31.0 nm). For the first time, very large β values of PtNFs are presented. Abstract : Platinum nanoflowers (PtNFs) were elaborated using the seed-mediated growth technique applied to monodisperse platinum nanoparticles (∼3.0 nm) synthesized by the chemical reduction method. The X-ray diffraction pattern confirmed the formation of face-centered-cubic platinum nanocrystals. We report the Harmonic Light Scattering (HLS) properties of PtNFs for six different diameters (∼7.0; 8.0; 10.0; 14.0; 20.0 and 31.0 nm). From these HLS data we infer, for the first time, large hyperpolarizability β values of PtNFs. These very high β values of PtNFs are assigned mainly to highly corrugated surfaces for nanoparticles with irregular shapes.